Upaya Manajer dalam Mengambil Keputusan Pemberian Pinjaman/LDR dan Mengatasi Permasalahan Kredit Macet/NPL - Kholid Farid (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2015)
This research generally aims to highlight the existence of the cooperative. One sector of the Indonesian nation's economic strength, which has a rapidly growing need special attention in the implementation of its operations. Force to be dealing directly with the public so as to understand laments faced by these communities as a form of the impingement kebutuhanya provide a portion of its own in penangananya. The impact of movements performed resulted in a wide range of issues that have to be borne, but if this kind is not to be taken seriously, then the pillars of the nation's economic strength will partially collapse. One of the problems faced, is the capital of cooperatives is not smooth, it caused some communities to meet tanggunganya, namely to pay for the debts borrowed does not work properly, it can be said on the level of profitability of the cooperative will be disrupted. It can be explained that influence the behavior of a benchmark as well as the educational background. Results of research conducted on the primary cooperatives in the district Demak with independent variables 5C on the effectiveness of loan repayment problem LDR partially there is an influence and an emphasis on non-performing loans/NPL, it can be seen from the respective results of t-count value which has a significance value less than 0.05